Antiparasitic Properties of Propolis Extracts and Their Compounds. Issue 9 (28th July 2021) - de L. Paula, Lucas A.; Cândido, Ana C. B. B.; Santos, Mario F. C.; Caffrey, Conor R.; Bastos, Jairo K.; Ambrósio, Sérgio R.; Magalhães, Lizandra G.
Abstract: Propolis is a bee product that has been used in medicine since ancient times. Although its anti‐inflammatory, antioxidant, antimicrobial, antitumor, and immunomodulatory activities have been investigated, its anti‐parasitic properties remain poorly explored, especially regarding helminths. This review surveys the results obtained with propolis around the world against human parasites. Regarding protozoa, studies carried out with the protozoa Trypanosoma spp. and Leishmania spp. have demonstrated promising results in vitro and in vivo. However, there are fewer studies for Plasmodium spp., the etiological agent of malaria and less so for helminths, particularly for Fasciola spp. and Schistosoma spp. Despite the favorable in vitro results with propolis, helminth assays need to be further investigated. However, propolis has shown itself to be an excellent natural product for parasitology, thus opening new paths and approaches in its activity against protozoa and helminths. Abstract :